Influence of glazing area on optimum thickness of insulation for different wall orientations - Ozel, Meral (Pergamon-Elsevier Science Ltd, 2019)
In this paper, influence of glazing area on optimum insulation thickness is numerically investigated considering wall orientations in the climatic conditions of Elazig, Turkey. For this aim, annual heating and cooling transmission loads are calculated according to the glazing area percentage (GAP) on the wall having various insulation thicknesses. Calculations are repeated for different wall orientations and two types of glazing (single glass and double glass) by varying GAP from 0 to 100%. Then, the transmission loads are used to determine the optimum thickness of insulation. It is obvious that as GAP increases, the optimum insulation thicknesses and energy savings decrease for all wall orientations and two types of glazing while payback periods increases. The results show that optimum insulation thicknesses of a south-facing wall are obtained to be 8.5, 6.5, 5.5 and 4 cm for values 0%, 20%, 40% and 60% of GAP in case of single glazing, respectively while they are obtained to be 8.5, 4, 3.5 and 2.5 cm in case of double glazing. Consequently, it is revealed that the glazing area in the wall, type of glazing and wall orientations have a significant effect on transmission loads and optimum insulation thickness.
Keywords: Annual heating arid cooling loads; Glazing area percentage; Type of glazing; Wall orientations; Optimum insulation thickness